From seagrass roots to saline soils: discovery of two new genera in Lulworthiales (Sordariomycetes) from osmotically stressed habitats - Martina Réblová; Jana Nekvindová; Ondřej Hynar; Martin Vohník (IMA Fungus)
As part of an ongoing study of marine fungi associated with seagrasses, we discovered a novel root-fungus symbiosis in the Indo-Pacific species Thalassodendron ciliatum from Mauritius. Culturing its mycobionts yielded dozens of morphologically and genetically uniform isolates, all representing a previously unknown fungus. A second undescribed fungus was isolated from saline soils in Czechia. Phylogenetic analyses based on three rDNA markers confirmed both taxa as distinct, hitherto unknown lineages within the Lulworthiales, which are introduced here as Thalassodendromyces purpureus gen. et sp. nov. and Halomyrma pluriseptata gen. et sp. nov., respectively. Both species developed characteristic structures under culture conditions that enabled their morphological characterisation: T. purpureus forms distinctive clusters of dark brown monilioid hyphae, while H. pluriseptata is characterised by holoblastic conidiogenesis and solitary, dark brown, multicellular conidia. Thalassodendromyces clustered in a strongly supported clade with Spathulospora, a parasitic genus of the red macroalga Ballia, while the closest relatives of Halomyrma were identified as the asexual genera Halazoon and Halophilomyces (nom. inval. Art. 40.7). An analysis of published metabarcoding ITS rDNA data from environmental samples in the GlobalFungi database indicated that H. pluriseptata is widely distributed across temperate, subtropical, and tropical regions in the Northern and Southern Hemispheres. The species exhibits a strong preference for aquatic biomes, particularly marine and estuarine, with a few records in terrestrial ecosystems. In contrast, no record of T. purpureus was retrieved from GlobalFungi, suggesting narrower ecological specialisation, a close association with its seagrass host, and/or a restricted geographical range. Our findings expand the ecological and phylogenetic scope of the Lulworthiales, bridging marine and terrestrial fungal communities, and highlight seagrass roots as an important source of novel symbiotic marine fungi. Recent discoveries of the Lulworthiales in saline inland soils challenge their marine exclusivity and raise important questions about their ecological plasticity, dispersal mechanisms, and adaptive strategies. In light of current observations, we discuss the taxonomic challenges of the Spathulosporales and the lulworthialean fungi, integrating molecular and morphological perspectives. We address the importance of combining morphological and molecular approaches to accurately delineate new fungal taxa, as well as the value of environmental DNA metabarcoding for uncovering cryptic fungal diversity and enhancing our understanding of fungal distribution and ecological functions.